Harta Negeri Dalam Perkawinan Adat Di Negeri Waraka, Kecamatan Teluk Elpaputih, Kabupaten Maluku Tengah - Pattianakotta, Adwil; Pattiasina, Johan (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
The issues addressed in this study are the process of implementing the Harta Negeri tradition in traditional marriages in Waraka Village and the meanings and values embodied in the Harta Negeri tradition for the community of Waraka Village. This research uses a descriptive qualitative method, gathering written or spoken words from people and observable behaviours to obtain a clear understanding and information about the implementation of the Harta Negeri tradition in traditional marriages in Waraka Village. The results of the study and the discussion of Harta Negeri in conventional marriages in Waraka Village, Teluk Elpaputih District, Central Maluku Regency, indicate that Harta Negeri is a tradition related to traditional marriages in Waraka Village. It is an obligation that must be fulfilled by a man from outside Waraka who marries a woman from Waraka. This tradition is one of the customary requirements in the marriage tradition of Waraka Village. However, this tradition does not apply when the marriage is between two people from within Waraka Village.